High-Power 810-nm Passively Mode-Locked Laser Diode With Al-Free Active Region - Quentin Gaimard; Guy Aubin; Kamel Merghem; Michel Krakowski; Olivier Parillaud; Sylvain Barbay; Abderrahim Ramdane (IEEE Photonics Journal, 2019)
We report on a mode locked semiconductor laser for high-power pulse generation in the 810-nm waveband. This is based on a novel GaAsP/GaInP single quantum-well structure, with Aluminum-free active region. Average output powers higher than 40 mW are reported in narrow ridge two-section devices. A 1.65-mm-long laser with 70 μm saturable absorber yields a stable mode locked regime at a 23-GHz repetition rate as evidenced by a record low RF linewidth of 75 kHz over a wide range of gain currents. Other laser dynamics are also reported at lower frequencies.